PENGUATAN LITERASI MEDIA SISWA SMA MELALUI CRITICAL VIEWING PADA POP CULTURE GLOBAL - Febri Dhany Triwibowo; Diah Soelistyowati; Pipiet Furisari; Budi Santoso; Ketut Purwantoro (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2026)
The massive influx of popular culture products among teenagers is often accepted passively without critical filters, resulting in vulnerability to information bias and global cultural hegemony. This community service activity aims to strengthen the critical literacy of students at SMA Mardisiswa Semarang through the critical viewing method. The implementation followed four stages: planning, partner identification, training through dialogic discussions and case studies, and reporting. The participants consisted of 32 twelfth-grade students. Data were collected through participatory observation and analyzed using a descriptive qualitative approach. The results demonstrated a significant transformation in the students' mindset, evolving from passive consumers into critical viewers. Students successfully improved their methodological skills in deconstructing visual messages, identifying agendas behind media content, and mitigating psychological impacts such as the Fear of Missing Out (FOMO) phenomenon. The use of popular culture texts as a learning instrument is effective in building students' sovereignty of thought and mental resilience in the era of information disruption.